2019
DOI: 10.1093/ndt/gfy409
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and long-term outcome in primary distal renal tubular acidosis

Abstract: Long term follow-up from this large dRTA cohort shows an overall favourable outcome with normal adult height for most and no patient with CKD 5. Yet, 82% of adult patients have CKD 2-4. Importance of adequate metabolic control was highlighted by better growth and renal function but was achieved in only half of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 32 publications
6
64
2
1
Order By: Relevance
“…Consequently, disturbances of acid-base balance are potentially catastrophic and can include dysrhythmias, apnea, coma, and death (46). And even relatively mild forms of distal RTA reveal that acidosis is associated not only with rickets and nephrocalcinosis/urolithiasis, but also with more general symptoms, such as impaired growth (47).…”
Section: Acid-base Homeostasismentioning
confidence: 99%
“…Consequently, disturbances of acid-base balance are potentially catastrophic and can include dysrhythmias, apnea, coma, and death (46). And even relatively mild forms of distal RTA reveal that acidosis is associated not only with rickets and nephrocalcinosis/urolithiasis, but also with more general symptoms, such as impaired growth (47).…”
Section: Acid-base Homeostasismentioning
confidence: 99%
“…Here, we report data on the transport activity of band 3 in RBCs and on the membrane/ cytoskeleton relationship, as well as of RBC shape and hemoglobin concentration. Other reports have also shown that SLC4A1 gene mutations are the main observed anomalies in dRTA, not only in Europe, 18 but also in south Asia. 36 Obvious hematological anomalies appear to be present only if patients carry the specific SAO anomaly, 23 which is consistent with our findings.…”
Section: Clinical Researchmentioning
confidence: 82%
“…Nonetheless, this is the first report of in-depth assessment of RBC membrane disorders in patients with AE1-related dRTA. Very recently, an international cohort of dRTA patients was reported with many data on both the phenotypic diagnosis and evolution, 18 but the authors did not collect any hematological data. Previous studies that focused on the correlation between hematological and renal involvements of AE1 mutations were performed in patients carrying recessive mutations (mostly p.G701D) and the specific SAO deletion.…”
Section: Clinical Researchmentioning
confidence: 99%
“…ATP6V1B1 and ATP6V0A4 encode the B1 and A4 subunits of the apical H + -ATPase pump, that is, the proton pump, in α-intercalated cells, respectively, and mutations in these genes cause autosomal recessive (AR) forms of dRTA with or without sensorineural hearing loss 6,7) . In a recent large multicenter study by the European dRTA Consortium, the prevalence of hearing loss was 88% in patients with ATP6V1B1 mutations and 36% in patients with ATP6V0A4 mutations 8) . SLC4A1 encodes the basolateral anion (Cl − /HCO 3 − ) exchanger 1 (AE1) 9) .…”
Section: Discussionmentioning
confidence: 98%